INTERNALISASI REVOLUSI MENTAL: Studi Analisis Deskriptif Siswa SMP Plus Ma’arif NU Pangandaran - Hidayat, Yayat (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
The focus of this study is, "How is the Internalization of the NU Middle School Student Mental Revolution Ma'arif Pangandaran?". This type of research includes descriptive qualitative research, namely research activities carried out on certain objects clearly and systematically. While the method used is a qualitative approach. This study aims to describe the Internalization of the NU Plus Middle School Mental Revolution Ma'arif Pangandaran. Research results: 1). Internalization is defined as appreciation, deepening, exile, combining or uniting attitudes, standard behavior, opinions and so on in the personality. 2). Mental Revolution is a transformation of ethos, which is a fundamental change in mentality, ways of thinking, ways of feeling and ways of trust, all of which are manifested in everyday behavior and actions. This ethos concerns all aspects of life, ranging from economics, politics, science to technology, art, religion, etc., 3). The internalization of the Mental Revolution is an in-depth process of the values of the Mental Revolution that runs in NU Plus Middle School Ma'arif Pangandaran. The process of internalization is very important in the Mental Revolution. Because the Mental Revolution is part of the education of values. The focus of this study is, "How is the Internalization of the NU Middle School Student Mental Revolution Ma'arif Pangandaran?". This type of research includes descriptive qualitative research, namely research activities carried out on certain objects clearly and systematically. While the method used is a qualitative approach. This study aims to describe the Internalization of the NU Plus Middle School Mental Revolution Ma'arif Pangandaran Research results: 1). Internalization is defined as appreciation, deepening, exile, combining or uniting attitudes, standard behavior, opinions and so on in the personality. 2). Mental Revolution is a transformation of ethos, which is a fundamental change in mentality, ways of thinking, ways of feeling and ways of trust, all of which are manifested in everyday behavior and actions. This ethos concerns all aspects of life, ranging from economics, politics, science to technology, art, religion, etc., 3). The internalization of the Mental Revolution is an in-depth process of the values of the Mental Revolution that runs in NU Plus Middle School Ma'arif Pangandaran. The process of internalization is very important in the Mental Revolution. Because the Mental Revolution is part of the education of values.